Optimal water resource planning under fixed budget by interval-parameter credibility constrained programming - Zhang, Y. M.; Huang, G. H. (Engineering optimization, 2011)
In this study, an interval credibility constrained programming (ICCP) was developed through introducing the concept of intervals into credibility constrained programming framework. Interval credibility levels can help decision makers to reflect uncertainties of preferences. By ICCP, a water resource planning model with fixed fuzzy budget was developed for supporting the planning of agriculture development and environmental protection. Surface and ground water were planned for regional irrigation in wet and normal seasons. For the interval credibility preference, best and worst cases were analysed. The tradeoff between the budget and the benefit were studied by sensitive analysis. The results showed that the current water resource budget is reasonable.